Narrativas sobre la comunicación en el noviazgo durante la pandemia por COVID-19. (2023)
This research seeks to analyze the narratives that five people in emerging adulthood, who are between 20 and 25 years of age, build through their experience in the face of communication as a couple during the COVID19 pandemic. The research is qualitative, using a semi-structured interview as an information construction technique. The narratives are articulated in three categories: Strategies and media, dynamics of exchange and courtship during confinement.